Hibridos dobles de maiz formados con lineas mejoradas por seleccion gametica y retrocruza - Navarro, E.=700 1 Burciaga, G.; Gonzalez, S.; Vega, M.C.; Morones, R.; Sandoval, E.
(En, Es)
ilus., 11 ref.
Keywords: ZEA MAYS; FITOMEJORAMIENTO; HIBRIDOS F2; HIBRIDACION; SELECCION; RETROCRUZAMIENTO; CARACTERISTICAS AGRONOMICAS; RENDIMIENTO; COSTA RICA; SELECCION GAMETICA